User interfaces for human robot interactions with a swarm of robots in support to firefighters - Gancet, Jeremi; Motard, Elvina; Naghsh, Amir; Roast, Chris; Arancon, Miguel Munoz; Marques, Lino (2010 IEEE International Conference on Robotics and Automation, 2010)
There are many different forms of human-robot interactions, allowing a team of humans and robots to take advantage of skills of each team member. A developing area of research is focused upon the potential of robot swarms working in emergency settings. In particular we consider a swarm of robots that are capable of supporting and enhancing fire fighting operations co-operatively. This paper outlines some of the key characteristics of this emergency setting, robot swarms within it and the work conducted to develop effective human-robot interaction.